PEMANFAATAN JARINGAN PENGGERAK SEKOLAH MADRASAH MUHAMMADIYAH (JPSM) DALAM BENCHMARKING MADRASAH MUHAMMADIYAH DI PURBALINGGA - Siswogo Siswogo (STAI Sufyan Tsauri Majenang, 2020)
JPSM is a place for teachers and school principals to have a desire to cooperate in accelerating the progress of their respective schools. One of the JPSM programs in Purbalingga is to help bridge the madrasa benchmarking process. Benchmarking Muhammadiyah madrasa in Purbalingga is a strategy to improve madrasa quality. Improving the quality of Muhammadiyah madrasa has implications for the level of public trust, indicated by an increase in the number of students. This research uses a qualitative approach. The research method used is descriptive method, describing and describing the phenomena that exist, both natural and engineering, pay more attention to the characteristics, quality, interrelationships between activities. Data collection techniques with interview studies with JPSM administrators, principals and madrasa teachers; study of madrasah benchmarking data, data on the number of students, madrasah achievement data, and JPSM profiles; and Madrasa internal environmental observational studies. The results showed that; first, JPSM is beneficial for madrasah progress, namely in an effort to improve madrasa quality through benchmarking activities; secondly, benchmarking can improve the quality of madrasas, which is suspected to have increased the number of students.